马中少儿出版社经营文化研究 ——以红蜻蜓和浙江少儿出版社为例 (The Management Culture Of Juvenile And Children Book Publishers In Malaysia And China : A Case Study Of Odonata Publishing Sdn Bhd And Zhejiang Juvenile And Children’s Publishing House) - Wang, Zhenghui (2019)
In recent years, the China-Malaysian culture industrial cooperation has been deepening. As a successful case of the exchange and cooperation between Malaysia and China, the Chinese Juvenile and children’s publishing industry has lead to the concern of nongovernmentals and governments. It is believed that the management culture of the Chinese Juvenile and children's publishing in both countries have the following characteristics. Firstly, the management culture of both countries’ Chinese Juvenile and Children's Publishing is adaptable. Due to the multi-ethnic culture, Malaysia Chinese Juvenile and Children's Publishing operate in a mild and moderate manner yet outstanding performance. Such is Odonata Publishing Sdn Bhd management culture is very representative。On the other hand, the Chinese Juvenile and Children's Publishing is much affected by political factors. Zhejiang Juvenile and Children's Publishing House was one of the Chinese Juvenile and Children's Publishing founded under the reformation period. Secondly, under the impact of online sales Malaysia and China Chinese Juvenile and Children's Publishing is more concerned of service rendered and richer content of children's books. Whereas the China Juvenile and children's Publishing based more on professional networking and sales operators. For example, dangdang provides more customer delivered value for readers through its online business model. V Similarly, Malaysia's largest Juvenile and Children's book seller Popular Bookstore offers a range of online sales services but still behind China. Thirdly, the development of Children's literature as an important content of the Malaysia Chinese Juvenile and Children's Publishing is never smooth. Nevertheless, the development of China Children's literature has gone through a process as “attachment” to “independence”. Though the development of both parties is difficult, various supports from all walks have contribute much to the development of the Children's literature. In particular, the awards and incentives given by the Chinese government. Fourthly, the management culture has become an important aspect of the cultural development of China and Malaysia Chinese Juvenile and Children's Publishing. The management culture of China Juvenile and Children's Publishing house reflects the emphasis on humanistic spirit and the shaping of brand culture. Such as Zhejiang Juvenile and Children's Publishing House emphasizes international brand image building and deepen cultural creative concepts, these factors Effectively enhance its operating power. The management culture of Malaysian Chinese Juvenile and Children's Publishing emphasizes on reading culture and flexibility. Odonata Publishing as the market leader and its management culture be recongnized. Lastly, creative business model has become an important factor of both Malaysia and China Juvenile and Children's Publishing's management culture. China Juvenile and Children's Publishing focuses on management Diversified innovation. Such as Zhejiang Juvenile and Children's Publishing House actively innovates its management model to enhance its brand awareness. On the other hand, Malaysia Chinese Juvenile and Children's Publishing actively develops its business models to adapt the national conditions, Odonata Publishing actively carry out public speeches in schools, cross-border cooperation, and promotion of international marketing processes. These enhanced its influence in domestic and foreign markets. Despite differences in operating environment, process of material civilizatio n and spiritual civilization and characteristics of business culture performance, VI both Malaysia and China Juvenile and Children's Publishing practice concrete e mbodiment of spiritual civilization and material civilization and they meet the needs of their Juvenile and Children's reading market. This study aims to provid e some references for both Malaysia and China Juvenile and Children's publishing industry.